The Burden Cancer-Related Deaths Attributable to High Body Mass Index in a Gulf Cooperation Council: Results from the Global Burden of Disease Study 2019 - Majed Ramadan; Rbab M. Bajunaid; Sereen Kazim; Noara Alhusseini; Ali Al-Shareef; Nourah Mohammed ALSaleh (Springer, 2024)
Abstract Background BMI has been reported to be a major risk factor for the increased burden of several diseases. This study explores the burden of cancer linked to high body mass index (BMI) in Gulf Cooperation Council (GCC) countries and assesses the correlation with Socio-demographic Index (SDI). Method Using Global burden of disease (GBD) 2019 data, the authors quantified cancer burden through mortality, DALYs, age standardized mortality rate (ASMR), and age standardized DALYs rate (ASDR) across sexes, countries, cancer types, and years. Spearman's correlation tested ASMR against SDI. The authors estimated 95% uncertainty limits (UIs) for population attribution fraction (PAFs). Results Between 1990 and 2019, all six GCC countries showed increased number of the overall cancer-related deaths (398.73% in Bahrain to 1404.25% in United Arab Emirates), and DALYs (347.38% in Kuwait, to 1479.35% in United Arab Emirates) reflecting significant increasing in deaths, and burden cancer attributed to high BMI. In 2019, across GCC countries, pancreatic, uterine, and kidney cancer accounted for 87.91% of the total attributable deaths associated with high BMI in females, whereas in male, colon and rectum cancer alone accounted for 26% of all attributable deaths associated with high BMI. Conclusion The study highlights the significant impact of high BMI on cancer burden in GCC countries. Moreover, the study identifies specific cancers, such as pancreatic, uterine, and kidney cancer in females, and colon and rectum cancer in males, as major contributors to attributable deaths, urging targeted prevention strategies at reducing weight and encouraging physical activity could greatly lessen the impact of diseases in the GCC countries.